It was not dead, it was resting! Notes to binding jurisprudence and anatocism - Polanco Gutiérrez, Carlos Enrique (2016)
In this paper the prohibition of capitalization of interest is analyzed in light of the recent binding jurisprudence of the Supreme Court (Cassations No 5128-2013-Lima and 2402-2012-Lambayeque, Sixth Civil Casatory Plenary) and the Constitutional Court (Resolution on Process No 214-2014-PA / TC), questioning whether that prohibition is, as noted by the Highest Courts in force or, on the contrary, in accordance with Circular No 021-2007-BCRP issued by the Central Reserve Bank that regulates the rate of interest applicable to people outside the financial system, the capitalization of interest is allowed.             The article makes an analysis of the contradictions that arise in our legal system, from an analytical-historical-doctrinal point of view, and questions about the convenience of starting a debate to repeal, modify or not art. 1249 of the Civil Code that prohibits anatocism, considering that such a rule would harm not only the debtor, but also the creditor, by making credit more expensive between individuals.